Conhecimento botânico tradicional sobre plantas medicinais no Quilombo Ipiranga, município do Conde-PB - Beltreschi, Letícia (2016)
For a long time, human societies have built a great deal of knowledge about the environments in which they are inserted, including knowledge about plant resources. This knowledge, ethnobotany's object of study, has guaranteed the survival of these populations as food, fuel and in the relief and cure of diseases. The present paper was structured in two chapters and had as it's objective to carry out an ethnobotanical survey on the knowledge and use of medicinal plants used by the inhabitants of the Ipiranga quilombola community, located in the south coast of Paraíba. In the first chapter, a survey of medicinal plant species was done according to the local knowledge, along with an analysis of the Usage Value and Informant Consensus Factor indexes. The interview method was applied through semi-structured questionnaires with a total of 100 community residents, 29 men and 71 women, between 20 and 90 years of age. the Usage Value and Informant Consensus Factor indexes were then estimated from the collected data. In the second chapter, a comparison between three different generations on the knowledge of medicinal plants was made, with a total of 171 individuals interviewed, and from the data, a Pearson correlation and an analysis of variance was accomplished. A total of 80 species, distributed in 66 genera and 38 botanical families, were identified. From the interviews, it was known that, in the majority, the leaves are the most used parts in the preparation of the medication, mainly through tea brewing. Most of the species used are grown in backyards. The medicinal species were indicated for the treatment of 66 diseases and classified into 14 categories of bodily systems. Regarding ethnobotanical knowledge among different generations, the results showed that older members of the group knew more species, as well as indicated a greater amount of uses for them.